Commitment in sport: The role of coaching style and autonomous versus controlled motivation - O`Neil, L.; Hodge, K. (Journal of Applied Sport Psychology, 2020)
This study examined the relationships among coaching style (autonomy-supportive, controlling), athlete motivation (autonomous, controlled), sport commitment (enthusiastic, constrained), and intention to continue in sport. Participants were 154 competitive football/soccer players (M = 22.21 years). Partial least squares structural equation modeling revealed positive associations among adaptive motivational (autonomy-supportive coaching style, autonomous motivation) and commitment (enthusiastic) variables. Similarly, positive links were found among maladaptive motivational (controlling coaching style, controlled motivation) and commitment (constrained) constructs. In addition, results indicated differential relationships between enthusiastic and constrained dimensions of commitment and intention to continue. Findings are discussed in terms of their theoretical and practical implications.